Mathematical Reasoning and Communication Levels Ability based on Gender Differences - St Zulaiha Nurhajarurahmah; Nurdin Arsyad (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
Issues about gender seems to be endless in various countries in the achievement of student learning outcomes, even in mathematics learning between male and female students. This qualitative research aims to explore the levels of mathematical reasoning and communication abilities of students who attend language class programs in senior high schools based on gender. Respondents were students who had abilities with different levels of ability, two each representing male and female students. Data analyze from the results of tests of mathematical reasoning and communication abilities and in-depth interviews using method and time triangulation techniques. The results show that female students are superior in reasoning and communicating than male students in solving math problems.